2013
DOI: 10.1016/j.watres.2012.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of microbial PCB degradation in sediment

Abstract: Bioremediation of polychlorinated biphenyls (PCBs) has been precluded in part by the lack of a cost-effective method to stimulate microbial degradation in situ. A common limitation is the lack of an effective method of providing electron donors and acceptors to promote in situ PCB biodegradation. Application of an electric potential to soil/sediment could be an effective means of providing electron-donors/-acceptors to PCB dechlorinating and degrading microorganisms. In this study, electrical stimulation of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…Thus, TOC removal increased with increase in applied voltage. This is in agreement with the observation of Chun et al [11] for the electrical stimulation of microbial PCB degradation in sediment. In recent years, several studies have reported that there was neither negative nor positive effects observed by applying current (3.14 A/m 2 ) on soil bacteria [14,32].…”
Section: Results and Discussion 31 Effect Of Applied Voltagesupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, TOC removal increased with increase in applied voltage. This is in agreement with the observation of Chun et al [11] for the electrical stimulation of microbial PCB degradation in sediment. In recent years, several studies have reported that there was neither negative nor positive effects observed by applying current (3.14 A/m 2 ) on soil bacteria [14,32].…”
Section: Results and Discussion 31 Effect Of Applied Voltagesupporting
confidence: 94%
“…That is, no removal of TOCs was observed in sterilized control. A similar observation has been reported for polychlorinated biphenyl (PCB) [11]. Also, there was no significant difference in the TOC concentration in sample Cathode Section soil with the distances from anode.…”
Section: Results and Discussion 31 Effect Of Applied Voltagesupporting
confidence: 86%
See 1 more Smart Citation
“…The basic concept of electro-assisted bioremediation of groundwater is to place polarized electrodes into the contaminated aquifer (Chun et al, 2013;Zhang et al, 2010). The contaminant removal could be electrochemically enhanced through several mechanisms.…”
Section: How Can Electrochemical Systems Contribute?mentioning
confidence: 99%
“…In order to treat wastewater in more sustainable way, bioelectrochemical system (BES) was introduced to achieve this goal for its resource recovery from wastewater and low energy consumption (Friman et al, 2013;Kong et al, 2014a;Liang et al, 2013;Wang et al, 2011). It has been demonstrated that BES is of great potential for the dechlorination, including reduction at anode and cathode (Aulenta et al, 2011;Chun et al, 2013;Huang et al, 2012;Kong et al, 2014b;Wen et al, 2013). Taking the reduction role of cathode into account, the electrons produced from anode are transferred via the external circuit to the cathode where it reduces the electron acceptor.…”
Section: Introductionmentioning
confidence: 99%